Under siege: counterterrorism and civil society in Hungary - Romaniuk, Scott Nicholas (Lexington Books, 2021)
Civil Society in Counter-Terrorism's Shadow -- The Security Prism -- Hostile Engagements -- Phantom Threats -- Return of the Security State -- Contested, Constrained, and Closing Spaces -- "Under Destruction".